Philosophical and Scientific Foundations for Constructing a Theory of Recurrence Mitigation in Cancer Patients - Priyanto Priyanto; Septiani Tri Sutrisni (Proceeding International Collaborative Conference on Multidisciplinary Science, 2026)
Cancer survivorship represents a growing public health concern, with more than 19 million cancer survivors worldwide confronting persistent psychological burdens. Fear of cancer recurrence (FCR) is the most prevalent and clinically significant unmet need, affecting 26%–56% of survivors and substantially impairing quality of life. This narrative review aimed to construct a theoretical foundation for recurrence mitigation among adult cancer patients by synthesizing philosophical, psychological, social, spiritual, and scientific evidence from 19 peer-reviewed articles published between January 2022 and June 2026, guided by the SANRA framework. Narrative synthesis yielded three major themes: (1) FCR as a multidimensional psychological distress construct; (2) adaptation, meaning in life, and spirituality as transformative mediating processes; and (3) psychological, social, and theoretical foundations underpinning resilience and adaptive coping. A theoretical construct was proposed delineating a sequential pathway: FCR → Psychological Distress → [Hope + Meaning in Life + Spirituality + Social Support] → Resilience → Adaptive Coping → Psychological Well-Being → Quality of Life → Recurrence Mitigation, with feedback loops. Seven testable theoretical propositions are presented. This construct provides a scientifically grounded, philosophically coherent, and empirically supported framework for nursing practice, psycho-oncological intervention, and future empirical validation.